Pengaruh K3 dan Motivasi Terhadap Produktivitas Kerja Karyawan di PT SS - Edy Soesanto; Lidia Margaretta Purba; Bunga Aprilia; Dwi Renaldy Putra; Sela Dwi Putri5 (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Previous and related analyzes are very important in analysis or in scientific articles. Prior research and related research support strengthening the concept and phenomenon of the relationship or influence on variables. The scientific article presents a description of the influence of K3 and motivation on employee productivity. The aim of these authors is to develop hypotheses regarding the effect of variables in further research. Research results based on literature reviews in several previous research journals prove that 1). Occupational Health and Safety (K3) has a positive and significant effect on Employee Productivity, 2). Work motivation has a significant positive effect on employee productivity, 3). Occupational Health and Safety (K3) and Work Motivation simultaneously have a significant effect on Employee Productivity.